Neuropathic Pain in Pancreatic Cancer: An Update of the Last Five Years - Raffaele Pezzilli (Gastroenterology Insights, 2021)
Pain is the main symptom of pancreatic cancer (pancreatic ductal adenocarcinoma, PDAC). Pain in pancreatic cancer may be visceral, somatic or neuropathic in origin. Pain is produced by tissue damage, inflammation, ductal obstruction and infiltration. Visceral nociceptive signals caused by damage to the upper abdominal viscera are carried along sympathetic fibers, which travel to the celiac plexus nerves and ganglia, which are found at the T12-L2 vertebral levels, anterolateral to the aorta near the celiac trunk. From here, the signals are transmitted through the splanchnic nerves to the T5-T12 dorsal root ganglia and then on to the higher centers of the central nervous system. Somatic and neuropathic pain may arise from tumor extension into the surrounding peritoneum, retroperitoneum and bones and, in the latter case, into the nerves, such as the lumbosacral plexus. It should also be noted that other types of pain might arise because of therapeutic interventions, such as post-chemoradiation syndromes, which cause mucositis and enteritis. Management with non-steroidal anti-inflammatory agents and narcotics was the mainstay of therapy. In recent years, celiac plexus blocks and neurolysis, as well as intrathecal therapies have been used to control severe pain, at times resulting in a decreased need for drugs, avoiding their unwanted side effects. Pain may impair the patient’s quality of life, negatively affecting patient outcome and resulting in increased psychological stress. Even after recognizing the negative effect of cancer pain on patient overall health, studies have shown that cancer pain is still undertreated. This review focuses on neuropathic pain, which is difficult to handle; thus, the most recent literature was reviewed in order to diagnose neuropathic pain and its management.